External capital flows in Latin America and the Caribbean in the 1990s : experiences and policies - Held, Gunther (1998)
Analyzes the experiences of a group of Latin American and Caribean countries with high inflows of external capital in 1992-1996 and places them within the context of the capital movements which have taken place in the region since 1977.